Structural Design Strategy and Active Site Regulation of High‐Efficient Bifunctional Oxygen Reaction Electrocatalysts for Zn–Air Battery - Liu, Xu; Zhang, Guangying; Wang, Lei; Fu, Honggang (Small (Weinheim an der Bergstrasse, Germany), 2021)
Zinc–air batteries (ZABs) exhibit high energy density as well as flexibility, safety, and portability, thereby fulfilling the requirements of power batteries and consumer batteries. However, the limited efficiency and stability are still the significant challenge. Oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are two crucial cathode reactions in ZABs. Development of bifunctional ORR/OER catalysts with high efficiency and well stability is critical to improve the performance of ZABs. In this review, the ORR and OER mechanisms are first explained. Further, the design principles of ORR/OER electrocatalysts are discussed in terms of atomic adjustment mechanism and structural design in conjunction with the latest reported in situ characterization techniques, which provide useful insights on the ORR/OER mechanisms of the catalyst. The improvement in the energy efficiency, stability, and environmental adaptability of the new hybrid ZAB by the inclusion of additional reaction, including the introduction of transition‐metal redox couples in the cathode and the addition of modifiers in the electrolyte to change the OER pathway, is also summarized. Finally, current challenges and future research directions are presented. Bifunctional oxygen electrocatalysts are the key components in rechargeable Zn–air batteries (ZABs). This review focuses on the design principles of Pt‐free electrocatalysts from the perspective of structural design and active site optimization. The latest advances of in situ techniques and other new strategies to improve the performance of ZABs are also discussed.